MICROSCOPIC ARCHITECTURE OF THE RESPIRATORY AND CONDUCTING SYSTEM OF THE LUNG OF NILE MONITOR - Abd-Elhafeezd, Hanan H.; Al Sulivany, Basim S.A.; Salah , Abdullah S.; Ali, Mennatallah; Mohamed, Nor E.; Soliman, Soha A. (Science Journal of University of Zakho, 2024)
Using semi-thin sections, the present investigation examined the microscopic characteristics of the lungs of the Nile monitor (Varanus niloticus). The lungs were composed of Intrapulmonary conducting airways and respiratory faveoli. Intrapulmonary airways originate from the terminal portion of the bronchus, which extends into the lung to create the bronchial tree. The bronchus was lined with pseudostratified ciliated epithelium composed of both ciliated and non-ciliated cells, and it was supported by plates of hyaline cartilage. The central lumen is surrounded by contractile fibers that contain smooth muscle cell bundles and are covered by ciliated and non-ciliated cells. The central lumen communicates with the faveoli. Separating adjacent faveoli are pulmonary trabeculae covered with various cell types, including type I pneumocytes, type II pneumocytes, and pulmonary macrophages. Some substantial pulmonary bronchi were also supported by small cartilage plate granules and lined with ciliated epithelium. Type I pneumocytes were flat cells, whereas type II pneumocytes had cuboidal cells with vacuolated cytoplasm. Surface irregularity and vacuolated cytoplasm were features of pulmonary macrophages. In addition, the connective tissue of the pulmonary septa contained immune cells, such as Mast and Eosinophils. In conclusion, the microstructure of the lung of the Nile monitor closely resembles that of other reptile species. However, the distinction between intrapulmonary cartilage palates and pulmonary septa raises the concept of species differentiation. In addition, the discovery of various types of pulmonary immune cells enhances the Nile monitor’s ability to persist in a variety of environments by enhancing its pulmonary immunity.